2013
DOI: 10.12659/msmbr.883737
|View full text |Cite
|
Sign up to set email alerts
|

Does pretreatment of bone marrow mesenchymal stem cells with 5-azacytidine or double intravenous infusion improve their therapeutic potential for dilated cardiomyopathy?

Abstract: BackgroundThis study was designed to investigate whether pretreatment of bone marrow mesenchymal stem cells (BMSCs) with 5-azacytidine (5-aza) or double intravenous infusion could enhance their therapeutic potential for dilated cardiomyopathy (DCM).Material/MethodsBMSCs were cultured for 2 weeks in the presence or absence of 5-aza and DCM serum. The cultured BMSCs (Groups 1 and 2), 5-aza-induced BMSCs (Groups 3 and 4), and medium alone (model control) were transplanted into 80 female Wistar rats by intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Bone marrow mesenchymal stem cells (BM‐MSCs) are stem cells residing within the bone marrow microenvironment. BM‐MSCs possess the following advantageous features: convenient collection, rapid proliferation, expansion in vitro, persistent self‐renewal capacities in vivo, and lack of questionable ethical issues . During the past few years, several studies have demonstrated that BM‐MSCs can localize to and/or participate in the development of new lung tissue .…”
Section: Introductionmentioning
confidence: 99%
“…Bone marrow mesenchymal stem cells (BM‐MSCs) are stem cells residing within the bone marrow microenvironment. BM‐MSCs possess the following advantageous features: convenient collection, rapid proliferation, expansion in vitro, persistent self‐renewal capacities in vivo, and lack of questionable ethical issues . During the past few years, several studies have demonstrated that BM‐MSCs can localize to and/or participate in the development of new lung tissue .…”
Section: Introductionmentioning
confidence: 99%
“…Effective gene expression and the resulting responses of the transfected cells are key factors for therapeutic outcomes of the procedure. Determining which cell type is more appropriate for application is critical, and factors such as differentiation potential, bone marrow mesenchymal stem cells, or differentiated cells like fibrochondrocytes should be considered [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of BMCs in impaired heart tissue could be multifunctional and multifactorial. Previous studies found that BMCs and bone marrow progenitor cells could secrete a series of cytokines that activate endogenous cardiac repair, such as activating resident cardiac progenitor cells and stimulating cardiomyocyte cell-cycle re-entry [ 37 , 38 ]. In addition, BMCs were involved in the process of neovascularization, inhibiting apoptosis of myocardial cells, and reducing inflammation through paracrine production of cytokines and growth factors [ 36 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%